Making Space for Young Children's Embodied Cultural Literacies and Heritage Languages with Dual Language Books - Si‘ilata, Rae K; Jacobs, Mary M; Gaffney, Janet S; Aseta, Martha; Hansell, Kyla (Wiley, 2023)
The Pasifika Early Literacy Project supports teachers to make space for the languages and cultures of Pacific children and families in early childhood settings in Aotearoa New Zealand. Dual-language books in five Pacific languages and English validate Pacific children's languages, literacies, and identities. We highlight teacher practices following professional learning and development workshops. Teachers are invited to challenge dominant monocultural notions of language and literacy that perpetuate educational inequities. Illustrations of early childhood teachers' innovations with Pacific children (aged 2–6 years) demonstrate how dual-language texts can be connected to families' embodied cultural literacies. Understandings of “literacy” and “reading” were expanded to include children's expressive modalities through oral and visual texts in heritage languages and English. This work highlights the role of teachers to connect, rather than replace, the worldviews, languages, and literacies of families with the pedagogical practices of early childhood settings.
Keywords: 3901 Curriculum and Pedagogy; 3903 Education Systems; 39 Education; Pediatric; 4 Quality Education; 1301 Education Systems; 1302 Curriculum and Pedagogy; Education; 3901 Curriculum and pedagogy; 3902 Education policy, sociology and philosophy; 3903 Education systems